2021
DOI: 10.31234/osf.io/5fpsa
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loneliness is associated with greater cognitive distance between the self and a close friend

Abstract: Loneliness describes the distressing experience associated with perceived social disconnection. Despite the clear links between loneliness and mental and physical health, relatively little is known about how loneliness affects cognition. To assess the effects of loneliness on cognitive distance between the self and others, participants completed an implicit memory task for adjectives encoded in relation to the self, a close friend, or a celebrity. We assessed item memory accuracy and sensitivity, and depth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 69 publications
(89 reference statements)
4
7
2
Order By: Relevance
“…Correlation analyses indicated that people who made more egocentric errors on the interactive reference assignment task and were more susceptible to egocentric interference on the visual perspective-taking task were more likely to self-report higher levels of loneliness and feelings of social isolation. This pattern is consistent with previous research that has shown a positive relationship between loneliness and a greater egocentric bias (Kokici et al, 2021) and suggests that people experience increasing levels of loneliness and feelings of social isolation with increasing age and that this age-related increase in loneliness leads to higher egocentric tendencies. However, mediation analyses showed that the effect of loneliness on egocentric tendencies in the interactive reference assignment task and visual perspective-taking task was not direct and instead only influenced these processes due to the increased experience of loneliness in older age.…”
Section: Discussionsupporting
confidence: 92%
“…Correlation analyses indicated that people who made more egocentric errors on the interactive reference assignment task and were more susceptible to egocentric interference on the visual perspective-taking task were more likely to self-report higher levels of loneliness and feelings of social isolation. This pattern is consistent with previous research that has shown a positive relationship between loneliness and a greater egocentric bias (Kokici et al, 2021) and suggests that people experience increasing levels of loneliness and feelings of social isolation with increasing age and that this age-related increase in loneliness leads to higher egocentric tendencies. However, mediation analyses showed that the effect of loneliness on egocentric tendencies in the interactive reference assignment task and visual perspective-taking task was not direct and instead only influenced these processes due to the increased experience of loneliness in older age.…”
Section: Discussionsupporting
confidence: 92%
“…They rate their feelings of connection to close others lower than non-lonely people [25] and also report less intimacy, comfort, and understanding, as well as more caution and distrust in their relationships [26]. When reflecting on the self or close others, lonely individuals show a reduced representational similarity between the self and other on a neural level [27] and they demonstrate a greater cognitive distance between the self and a friend [28]. However, does this mean they have different preferences regarding interpersonal space and distance?…”
Section: Introductionmentioning
confidence: 99%
“…Regarding valence effects on metamemory, inconsistent findings have been presented. For example, greater metacognitive sensitivity has been shown for long term memory (a week) of positive items (Legrand et al, 2021) and for short-term memory (an hour) for negative items (Kokici et al, 2021). As metacognition reflects how we think about our own thinking, individuals with affective disturbances may present with diminished confidence in their ability, in line with previously discussed negativity biases or feelings of helplessness (Drueke et al, 2022).…”
Section: Concernsmentioning
confidence: 63%
“…An individual with high metacognitive sensitivity is highly confident for correct responses and expresses lower confidence for incorrect responses. Previous research suggests a SRE is also apparent in metamemory (Kokici et al, 2021). Regarding valence effects on metamemory, inconsistent findings have been presented.…”
Section: Concernsmentioning
confidence: 88%
See 1 more Smart Citation